Impact of COVID-19-related care disruptions on blood pressure management and control in community health centers - Margaret Meador; Fátima Coronado; Debosree Roy; R. Curtis Bay; Joy H. Lewis; Jessica Chen; Rachel Cheung; Christopher Utman; Judith A. Hannan (BMC, 2022)
Abstract Background Uncontrolled hypertension is a leading risk factor for cardiovascular disease. To ensure continuity of care, community health centers (CHCs) nationwide implemented virtual care (telehealth) during the pandemic. CHCs use the Centers for Medicare & Medicaid Services (CMS) 165v8 Controlling High Blood Pressure measure to report blood pressure (BP) control performance. CMS 165v8 specifications state that if no BP is documented during the measurement period, the patient's BP is assumed uncontrolled. Methods To examine trends in BP documentation and control rates in CHCs as telehealth use increased during the pandemic compared with pre-pandemic period, we assessed documentation of BP measurement and BP control rates from December 2019 - October 2021 among persons ages 18-85 with a diagnosis of hypertension who had an in-person or telehealth encounter in 11 CHCs. Rates were compared between CHCs that did and did not implement self-measured BP monitoring (SMBP). Results The percent of patients with hypertension with no documented BP measurement was 0.5% in December 2019 and increased to 15.2% (overall), 25.6% (non-SMBP CHCs), and 11.2% (SMBP CHCs) by October 2021. BP control using CMS 165v8 was 63.5% in December 2019 and decreased to 54.9% (overall), 49.1% (non-SMBP), and 57.2% (SMBP) by October 2021. When assessing BP control only in patients with documented BP measurements, CHCs largely maintained BP control rates (63.8% in December 2019; 64.8% (overall), 66.0% (non-SMBP), and 64.4% (SMBP) by October 2021). Conclusions The transition away from in-person to telehealth visits during the pandemic likely increased the number of patients with hypertension lacking a documented BP measurement, subsequently negatively impacting BP control using CMS 165v8. There is an urgent need to enhance the flexibility of virtual care, improve EHR data capture capabilities for patient-generated data, and implement expanded policy and systems-level changes for SMBP, an evidence-based strategy that can build patient trust, increase healthcare engagement, and improve hypertension outcomes.